Obtenção e caracterização do compósito de polipropileno reciclado com fibra de palmeira-real (Archontophoenix cunninghamiana) - Sá, Bruno de Souza Ribeiro (2019)
This research aimed to obtain Recycled PP/Fiber composite of Australian Royal Palm (Archontophoenix cunninghamiana) and further characterization of mechanical and thermal properties. Samples were produced by extrusion/injection with the formulation of mass ratio 20/80 of Royal Palm fibers and Recycled PP. Virgin PP (H 301) was used as control. The samples were analyzed by flow index (MFI), tensile test, IZOD impact test, differential scanning calorimetry (DSC), thermogravimetry (TGA) and scanning electron microscopy (SEM). The recycled PP/Royal Palm fiber and PP H301 presented very close values of melt indexes, 9.5 (g/10min) and 9.2 (g/10min), respectively. The stiffness of recycled PP/Royal Palm fiber (1471 MPa) was higher than PP H301 (1350 MPa). The tensile strength of recycled PP/Palm fiber was 25% lower than the PP H301. Elastic modulus values of recycled PP/Royal Palm fiber are quite similar. Impact resistance of recycled PP/Palm fiber composite is higher (35 J/m) than PP H301 (33 J/m). DSC curves showed that the insertion of 20 wt-% of Royal Palm fiber into PP H301 or into Recycled PP did not affected substantially the melting point and crystallization temperature, relative to the respective thermoplastic resin. TGA analysis showed that the recycled PP/Royal Palm fiber composite possesses higher thermal stability than PP H301, with initial degradation temperature (Ti) of 302 ºC and 275 ºC, respectively. Morphology through SEM images showed adhesion between PP H301 and Royal Palm fibers, being the adhesion higher in recycled PP/Royal Palm composite. The recycling of polypropylene and further mixing with Royal Palm fibers, which is a byproduct of palm heart extraction, to produce recycled PP/Royal Palm fiber composite proved to be an alternative for reducing the environmental impacts generated by the disposal of thermoplastic resins. It is also viable from the economic point of view, because the Royal Palm fibers possess lower cost as compared to recycled thermoplastic resin.